RESÍDUOS SÓLIDOS ORGÂNICOS NO MUNICÍPIO DE FELIZ / RS: AVALIAÇÃO E DIRETRIZES PARA UM GERENCIAMENTO MAIS SUSTENTÁVEL - Baldauf, Eduardo; Timm, Janaine Fernanda G.; Giugliani, Joana; Pires, Maíra O.; Sattler, Miguel Aloysio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents an analysis of the generation of Urban Solid Wastes in the city of Feliz - RS, focused on residential buildings, in order to identify the potential for exploitation of those classified as easily biodegradable organic matter for composting or animal feed purposes. Thus, it would be possible to divert annually tons of wastes usually sent to landfills, thus promoting diverse environmental benefits, including the reduction of the use of chemical fertilizers in crops and gardens, as well as economic benefits for low income families that would benefit from this by-product. The creation of this new and more sustainable scenario would require from the municipal government some strategies that would contribute to the environmental awareness of the population, so that it becomes more aware of the possibilities of use and retention of waste generated, both in their homes or in commercial establishments.